A review of the current Philippine energy policy in the context of the viability of wind energy as a significant component of the country's energy mix - Catalla, Jonathan S.; Posadas, Roger (Quezon City University of the Philippines Diliman, 2011)
A scan of existing policies related to the commercialization of wind power in the Philippines shows that there are several factors that may either propel it to widespread success or relegate it to monumental failure. With the signing of Republic Act 9513, otherwise known as the Renewable Energy Act of 2008, the country hopes to leverage its abundant renewable energy resources in the alleviation of its fossil fuel dependence. RA 9513 offers many incentives for potential renewable energy developers, such as feed-in-tariffs for RE power producers, must-dispatch prioritization of all power produced, and seven year tax incentives on actual power generation and equipment importation. Wind energy is one such non-depleting and renewable resource that the country possesses. In the most recent update of the Philippine Energy Plan, the Department of Energy has ambitiously set the goal of being ranked number one in Southeast Asia in terms of wind power capacity by 2014. Technological and environmental factors may affect the widespread commercialization of wind power. Technologically, we do not yet possess the know-how of designing and building wind turbines or operating utility scale wind farms, although there is one such facility existing in the country as of this writing. Geographically, wind power is most frequently site-specific - only about twenty percent of the sites studied so far show indications of sustained winds that can viably support the operation of a reliable power plant based on wind power. This translates to inefficient cost models of connecting to the national power grid. This paper makes use of the technological innovation system framework in analyzing the interactions between the actors playing key roles in this arena. Comparative discussions will show where these countries lead the Philippines in terms of the different components of the framework. We will attempt to point out what specific factors are lacking within each component in such a way that wind power technology commercialization may lead to failure if not addressed. After this framework-based analysis, the paper will also attempt to comment on possible policy observations in the long term to ensure the successful commercialization of wind power technology. The author's recent employment with a start-up government owned corporation on renewable energy during the writing of this paper has offered unique insider insights on the current national energy situation.
In partial fulfillment of the requirements in TM 299.2.
Thesis
Keywords: Energy policy -- Philippines; Wind power; Wind energy; Philippine energy; Energy policy